Faktor-Faktor yang Mempengaruhi Pengetahuan Ibu Hamil Tentang Makanan yang Mengandung Zat Besi di Puskesmas Peureulak Aceh Timur Tahun 2024 - Khairul Nisak; Ester Simanullang; Febriana Sari (Lembaga Pengembangan Kinerja Dosen, 2024)
Anemia in pregnant women can increase the risk of premature birth, maternal and child death, and infectious diseases. Iron deficiency anemia in mothers can affect the growth and development of the fetus/baby during pregnancy and afterward. The aim of the research is to determine the factors that influence pregnant women's knowledge about foods containing iron at the Peureulak Health Center, East Aceh in 2024. The type and design of this research is Correlative Descriptive with a Cross Sectional Study approach, namely to see the relationship between the Dependent and Independent Variables. Independent variables are factors that influence pregnant women's knowledge and dependent variables (food containing iron). The sampling technique in this study was accidental, meaning that by chance anyone who came to the Peureulak Health Center for Ante Natal Care (ANC) visits during March and April 2024 would be sampled. Research results There is a relationship between knowledge of pregnant women about the meaning of containing iron at the Peureulak Health Center, East Aceh in 2024 with age, education, occupation, gravida and source of information